2009
DOI: 10.1074/jbc.m807500200
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile-specifier Proteins Involved in Glucosinolate Hydrolysis in Arabidopsis thaliana

Abstract: Glucosinolates are plant secondary metabolites present in Brassicaceae plants such as the model plant Arabidopsis thaliana. Intact glucosinolates are believed to be biologically inactive, whereas degradation products after hydrolysis have multiple roles in growth regulation and defense. The degradation of glucosinolates is catalyzed by thioglucosidases called myrosinases and leads by default to the formation of isothiocyanates. The interaction of a protein called epithiospecifier protein (ESP) with myrosinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 61 publications
3
103
0
1
Order By: Relevance
“…The second is the nitrile-specifier protein NSP2 (spot 49 in Figs. 5 and 7A) involved in the hydrolysis of glucosinolates to nitrile, sulfur, and sulfate (Wittstock and Halkier, 2002;Grubb and Abel, 2006;Kissen and Bones, 2009), which suggests an increased catabolism of these compounds in sultr3;4 developing seeds. Glucosinolates are transported from all parts of the plant into developing seeds, and most of the glucosinolates contained in oilseeds are located in the embryo (Josefsson, 1970;Gijzen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The second is the nitrile-specifier protein NSP2 (spot 49 in Figs. 5 and 7A) involved in the hydrolysis of glucosinolates to nitrile, sulfur, and sulfate (Wittstock and Halkier, 2002;Grubb and Abel, 2006;Kissen and Bones, 2009), which suggests an increased catabolism of these compounds in sultr3;4 developing seeds. Glucosinolates are transported from all parts of the plant into developing seeds, and most of the glucosinolates contained in oilseeds are located in the embryo (Josefsson, 1970;Gijzen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nitrile-specifier protein 2 is abundant in both dry and germinating Arabidopsis seeds and is also progressively translated (supplemental Tables S1 and S7). Through in vitro assays on mature seed extracts, nitrile-specifier protein 2 was shown to preferentially promote nitrile production upon glucosinolate breakdown, thereby allowing efficient remobilization of the sulfur and nitrogen contents (106). Thus, glucosinolate degradation during Arabidopsis seed germination could represent a significant source of sulfur and nitrogen, thereby fueling the sulfur amino acid metabolism essential for germination (107,108).…”
Section: Discussionmentioning
confidence: 99%
“…ITCs of allyl and 3-butenylglucosinolates were more attractive than those of simple nitriles and epithionitriles in P. rapae [59]. Kissen and Bones [60] also found that the introduction of Brassica nigra GSL-ALK gene into Arabidopsis ecotype col-5 plants (normally producing methyl sulfinyl alkylGSL, GSL-ALK gene) leads to the conversion of 4-methyl sulfinyl butyl GSL in to 3-butenylGSL which, in turn, gets degraded into 3-butenylisothiocyanate upon infestation with B. brassicae. Further, these infested plants were shown to be more attractive to Diaeretiella rapae (Hymenaptera: Braconidae) than uninfested plants.…”
Section: As a Direct Toxinmentioning
confidence: 98%